2017
DOI: 10.1016/j.msea.2016.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the partial solutionisation of a high pressure die-cast Al-Mg-Zn-Si alloy for mechanical property enhancement

Abstract: High pressure die-casting alloys were not basically suitable for T6 treatment. The partial solution treatment was developed to enhance the mechanical properties for a new designed die-cast Al-Mg-Zn-Si alloy. The strengthening mechanism was that the Mg 32 (Al,Zn) 49 intermetallics and equilibrium MgZn 2 phase formed in the as-cast microstructure were partially dissolved into the α-Al matrix during solutionising and the fine semi-coherent η'-MgZn 2 phases were precipitated during subsequent aging. Consequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…T' and T'' phases) are often observed in Al-Mg-Zn alloys [5, 7, 8, 19, 20, 25, 26] [22, 23]. However, it was also reported that the precipitate in several cast Al-Mg-Zn alloys with non-negligible Cu or Si levels, including Al-10.2Mg-3.2Zn-2.7Si aged at 160°C [30], Al-8.1Mg-3.5Zn-2.6Si aged at 180°C [10] and Al-5Mg-3.09Zn-1.0Cu aged at 150°C [21], is g' phase. It indicates that the phase transformation between g' and T' or T'' phases in Al-Mg-Zn alloys maybe exists.…”
Section: Solidification Path and Microstructural Evolutionmentioning
confidence: 99%
“…T' and T'' phases) are often observed in Al-Mg-Zn alloys [5, 7, 8, 19, 20, 25, 26] [22, 23]. However, it was also reported that the precipitate in several cast Al-Mg-Zn alloys with non-negligible Cu or Si levels, including Al-10.2Mg-3.2Zn-2.7Si aged at 160°C [30], Al-8.1Mg-3.5Zn-2.6Si aged at 180°C [10] and Al-5Mg-3.09Zn-1.0Cu aged at 150°C [21], is g' phase. It indicates that the phase transformation between g' and T' or T'' phases in Al-Mg-Zn alloys maybe exists.…”
Section: Solidification Path and Microstructural Evolutionmentioning
confidence: 99%
“…The heat treatment of the die casting is realized while avoiding the foaming deformation of the casting, and the strength of the casting is improved by the low temperature solid solution aging. Wenchao Yang [8] studied a partial solution treatment process to improve the mechanical properties of die-cast Al-Mg-Zn-Si alloy which successfully increased the alloy ultimate tensile strength(UTS) from 350 MPa to 362 MPa, solutioning at 430°C for 1 h. However, in the study of Al-Mg-Zn-Si die-casting alloys, the effects of various elements such as Ti, Cu and Fe on the microstructure and properties of Al-Mg-Zn-Si die-cast alloys are lacking.…”
Section: Introductionmentioning
confidence: 99%